A novel method for the measurement of flow-induced platelet activation at nanoscale resolution level - Santos-Martínez, María José (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2009)
Background: Platelet aggregation Is essential for vascular haemostasis and thrombosis. Inhibition of platelet aggregation underpins the pharmacological and clinical effects of antiplatelet drugs. These effects are commonly quantified using methods and devices that assess platelet aggregation under static conditions in macroscale. However, current devices neither mimic the conditions found in human microvasculature nor detect microaggregates. Aim: To provide pharmacological characteristics of a novel method of flow- induced platelet aggregation using a commercially available nanoscale resolution device, the Quartz Crystal Microbalance with Dissipation (Q-Sense™ E4).
Keywords: Pharmacy, Ph.D.; Ph.D. Trinity College Dublin